Water extract of Artemisia ordosica enhances antioxidant capability and immune response without affecting growth performance in weanling piglets. Issue 6 (14th August 2019) - Xing, Yuanyuan; Wu, Yingzhao; Mao, Chenyu; Sun, Dengsheng; Guo, Shiwei; Xu, Yuanqing; Jin, Xiao; Yan, Sumei; Shi, Binlin
Abstract: The present experiment was conducted to investigate the effects of water extract of Artemisia ordosica (WEAO) on growth performance, antioxidant capability and immune response in weanling piglets. Seventy‐two 28‐day‐old weanling piglets were randomly allocated into four treatments with six replicate pens per treatment and three piglets per pen ( n = 18). These four treatment diets were formulated by adding 0, 250, 500 and 750 mg/kg WEAO to the basal diet. The experiment lasted for 28 days. Body weight and feed intake were measured. Blood samples were collected to determine immune and antioxidative parameters. The experimental results showed that WEAO supplementation improved the apparent nutrient digestibility of piglets in a linear or quadratic dose‐dependent manner. In addition, dietary WEAO quadratically increased serum concentrations of cytokines interleukin (IL)‐1, IL‐4, tumour necrosis factor (TNF)‐α, soluble surface antigen CD8 (sCD8), immunoglobulins (Ig)‐A and linearly increased serum concentrations of IL‐2, IL‐6, IgG, IgM. Furthermore, dietary WEAO linearly or quadratically decreased serum concentrations of malondialdehyde but quadratically increased activities of antioxidant enzymes and total antioxidative capacity. These results suggested that WEAO may prove useful as a natural phytogenic feed additive with antioxidative potential and could be incorporated into diets of piglets.